Functional amyloids from bacterial biofilms – structural properties and interaction partners. Issue 22 (23rd May 2022) - Akbey, Ümit; Andreasen, Maria
Abstract : Functional bacterial amyloids forming biofilms have unique structural characteristics while still being similar to pathological ones. Through many identified interaction partners, they emerge as complex and essential components of biofilms. Abstract : Protein aggregation and amyloid formation have historically been linked with various diseases such as Alzheimer's and Parkinson's disease, but recently functional amyloids have gained a great deal of interest in not causing a disease and having a distinct function in vivo . Functional bacterial amyloids form the structural scaffold in bacterial biofilms and provide a survival strategy for the bacteria along with antibiotic resistance. The formation of functional amyloids happens extracellularly which differs from most disease related amyloids. Studies of functional amyloids have revealed several distinctions compared to disease related amyloids including primary structures designed to optimize amyloid formation while still retaining a controlled assembly of the individual subunits into classical cross-β-sheet structures, along with a unique cross-α-sheet amyloid fold. Studies have revealed that functional amyloids interact with components found in the extracellular matrix space such as lipids from membranes and polymers from the biofilm. Intriguingly, a level of complexity is added as functional amyloids also interact with several disease related amyloids and a causative link has even been established between functional amyloids and neurodegenerative diseases. It is hence becoming increasingly clear that functional amyloids are not inert protein structures found in bacterial biofilms but interact with many different components including human proteins related to pathology. Gaining a clear understanding of the factors governing the interactions will lead to improved strategies to combat biofilm associated infections and the correlated antibiotic resistance. In the current review we summarize the current state of the art knowledge on this exciting and fast growing research field of biofilm forming bacterial functional amyloids, their structural features and interaction partners.